Analysis of the Carrying Capacity and Environmental Capacity of the Bukit Tangkiling Natural Park - Rasidi, Muhammad; Lautt, Bambang S.; Ludang, Yetrie; Usup, Sidik R.; Jaya, Adi (PT. Riset Press International, 2023)
The Bukit Tangkiling Park area was determined based on the Decree of the Minister of Agriculture of the Republic of Indonesia number: 046/Kpts/Um/1/1977 on January 25, 1997, with an area of 533 Ha. Bukit Tangkiling Nature Park has sloping lowlands, undulating to hilly terrain, and very steep slopes of 2% to 45% at 25 to 170 metres above sea level. Year-to-year tourism increases. An increase in tourist visits can damage natural resources and the environment by exceeding the carrying capacity and capacity of the environment. Cifuentes (1992)'s method is used to calculate the natural tourist environment's carrying capacity in protected areas. The assessment to determine the maximum number of visits to a tourist area is based on the physical, biological and management conditions in the tourist area by considering three main aspects; physical carrying capacity (PCC), real carrying capacity (RCC) and effective carrying capacity (ECC). The research was conducted with the aim of analyzing the value of the effective carrying capacity (ECC). The maximum number of tourists that can visit the Bukit Tangkiling Natural Tourism Park without disrupting the ecology. PCC = 219.063, RCC = 5.475, MC = 0.9, ECC = 4,927 people/day. ECC of 353 people/day. This value is less than the Nature tourist Carrying Capacity Value and does not harm the environment of the natural tourist region. This allows Bukit Tangkiling Park growth.